DIVERSIFICATION OF HORTICULTURAL FARMING IN FACING THE COVID-19 PANDEMIC: A CASE STUDY IN SIGI BIROMARU DISTRICT, CENTRAL SULAWESI - Ihdiani Abubakar; Siti Yulianty Chansa Arfah; Hardiyanti Sultan; Sultan Sarda (Universitas Tadulako, 2022)
Efforts to use land through cropping patterns or crop rotation, better known as farm diversification can be an alternative for farmers to maintain their farming during the COVID-19 pandemic. This pandemic affected commodity changes or changes in cropping patterns on farms cultivated by farmer. This study aims to analyze and describe the pattern of horticultural farming and the level of farmers’ incomes. The research was conducted in three villages in Sigi Biromaru District, namely Jono Oge Village, Lolu Village, and Sidera Village. The results show that there are no differences in the cropping patterns carried out by farmers in the pre-pandemic and pandemic periods. The cropping patterns include intercropping, multiple cropping, and relay cropping. The highest income per year is obtained by Jono Oge Village at IDR 12,054,600.00, followed by Lolu Village at IDR 8,099,262.40 and Sidera Village was IDR 4.416.600.00.